2017
DOI: 10.1063/1.4975965
|View full text |Cite
|
Sign up to set email alerts
|

Esterification of oil adsorbed on palm decanter cake into methyl ester using sulfonated rice husk ash as heterogeneous acid catalyst

Abstract: Palm Decanter cake (PDC) which is categorized as the waste from palm oil mill has been found to contain residual crude palm oil. The oil adsorbed on the PDC (PDC-oil) can be extracted and potentially used as feedstock for biodiesel production. Feedstock from waste like PDC-oil is burdened with high free fatty acids (FFAs) which make the feedstock difficult to be converted into biodiesel using basic catalyst. Therefore, in this study, a solid acid, RHA-SO 3 H catalyst was synthesized by sulfonating rice husk as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…From the experimental result, it was noticed that 8% of oil was regained from palm oil mill effluent and produced biodiesel possess a high cetane number and cloud temperature (59-60) and (10-13°C) respectively. Hindryawati, N. et al [18] used ultrasound method to convert residual oil from palm decanter cake (PDC) into biodiesel. It was found that about 11.3 wt.% of oil regained after 60 min.…”
Section: Production Of Biodiesel From Palm Oil By-products and Mill Effluent Using Flask Reactormentioning
confidence: 99%
“…From the experimental result, it was noticed that 8% of oil was regained from palm oil mill effluent and produced biodiesel possess a high cetane number and cloud temperature (59-60) and (10-13°C) respectively. Hindryawati, N. et al [18] used ultrasound method to convert residual oil from palm decanter cake (PDC) into biodiesel. It was found that about 11.3 wt.% of oil regained after 60 min.…”
Section: Production Of Biodiesel From Palm Oil By-products and Mill Effluent Using Flask Reactormentioning
confidence: 99%
“…Hindryawati et al (2017) used residual oil from palm decanter cake for 300 minutes to produce biodiesel, which achieved a yield of 70.2% [25]Ricca et al (2013).…”
mentioning
confidence: 99%